Surgical treatment of cataract and glaucoma in nanophthalmic eye – case report - Żarnowski, Tomasz; Pietraś-Trzpiel, Małgorzata; Chorągiewicz, Tomasz; Jurkowska, Justyna; Jünemann, Anselm; Rejdak, Robert (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Work presents surgical strategy in case of cataract and glaucoma in patient with simple nanophthalmus. Moreover optimal manner of calculation of the IOL and treatment in case of occurrence of complication from disturbed structure of eyeball. Surgical procedure included removal of cataract by using phacoemulsification, implantation of artificial Acri.Lyc Extreme lens, account from Haigis rule. Because of high intraocular pressure in early postoperative period we decided to implant Ahmed devices – children’s type with drain placed in posterior chamber combined with posterior vitrectomy. We obtained stabilization of intraocular pressure and effective visual acuity.